Glucose Control in Post-hemolytic-Uremic Syndrome Diabetes: A New Approach Offered by Sensor-Augmented Pump Therapy - Valeria Grancini; Federica Alessandra Vianello; Santo Colosimo; Santo Colosimo; Alessia Gaglio; Veronica Resi; Maura Arosio; Maura Arosio; Gianluigi Ardissino; Giovanni Montini; Giovanni Montini; Emanuela Orsi (Frontiers Media S.A., 2022)
We report the case of a 3-year-old girl admitted to her town emergency department for fever (39°C) associated with diarrhea, generalized edema, oliguria, and drowsiness. The blood test revealed metabolic acidosis, leucocytosis, increased inflammatory markers, anemia, thrombocytopenia, and acute kidney failure. Based on the diagnosis of hemolytic-uremic syndrome, the patient was referred to a third-level children hospital. Assisted ventilation, hemodialysis, and parenteral nutrition were instituted. The blood glucose levels increased above 200 mg/dl with peaks at 500 mg/dl. Islet auto-antibodies were negative and C-peptide was undetectable, thus ruling out the diagnosis of type 1 diabetes. Multiple-daily-injection insulin therapy was then instituted with the following regimen: Detemir 2 U once daily and Aspart 0.5 U if blood glucose >200 mg/dl. Despite the very low insulin dosage, the patient experienced frequent and severe hypoglycemic events during the following 24 h and was therefore switched to sensor-augmented pump therapy. Optimal glucose control was achieved without further hypoglycemic episodes. Moreover, thanks to the possibility to customize insulin therapy hour by hour during the day and the use of a pre-low glucose suspend system, glucose control was maintained even despite the continuous modifications in the nutritional scheme due to the multiple complications that arose during hospitalization. This rare case of post-hemolytic-uremic syndrome diabetes, treated with sensor-augmented therapy from its outbreak, suggests for the first time the potential of this therapeutic strategy in achieving glucose control without significant hypoglycemic episodes in children with secondary forms of diabetes associated with very low insulin requirement.